Early Detection of Preschool Children with ADHD and the role of mobile Apps and AI - Tsakou , Vasiliki; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder with the main symptoms of attention deficit, hyperactivity and impulsivity, to the extent that it creates or exacerbates existing behavioral problems and is a brake on a person's daily life.The process of early detection of developmental disorders is done with different diagnostic criteria, which are evaluated by the relevant interdisciplinary team in order to conclude if the child has ADHD and what therapeutic approach should be followed (3). It seems that many of the adverse long-term consequences that characterize ADHD can be avoided when an intervention is started in preschool, when the brain is likely to be more "plastic" and possibly prone to permanent modifications, and before complicating factors such as comorbid psychiatric disorders, academic failure and poor social and family relationships emerge, making successful treatment more difficult. The result of the study of the above researches confirms that the development of diagnostic tools, the interest of researchers and the awareness of parents through a child-centered pedagogical upbringing system makes the Early Detection of ADHD possible (8). The interest of teachers and parents has turned to prevention, Early Detection and Early Intervention while creating the idea of integration and social inclusion of children with problems(3).